Peaceful Islamist Mobilization in the Muslim World - Hwang, Julie Chernov. author. aut Link
XVIII, 235 p.
Keywords: In Peaceful Islamist Mobilization in the Muslim World: What Went Right , Julie Chernov Hwang presents a compelling and innovative new theory and framework for examining the variation in Islamist mobilization strategies in Muslim Asia and the Middle East.